Recent progress and applications in glycosaminoglycan and heparin research - Laremore, Tatiana N. (2009)
Heparin, the focus of this review, is a critically important anticoagulant drug produced from animal sources, which was contaminated last year leading to a number of adverse side effects, some resulting in death. Heparin is a highly acidic polysaccharide and a member of a family of biopolymers called glycosaminoglycans. The structure and activities of heparin are detailed along with recent advances in heparin structural analysis and biological evaluation. Current state-of-the-art chemical and chemoenzymatic synthesis of heparin and new approaches for its metabolic engineering are described. New technologies, including microarrays and digital microfluidics, are proposed for high-throughput synthesis and screening of heparin and for the fabrication of an artificial Golgi.